Further Studies on Dehydration of Prawns in Rotary Drum Dryer - BALACHANDRAN, K. K.; BOSE, A. N. (Fishery Technology, 1968)
The paper deals with studies made to modify the processof drying of prawns in rotary drum dryer reported by the authorsearlier. Prawns belonging to any species except M. monoceroscan be satisfactorily dried. With M. monoceros invariably considerableadherence of shell occurs. Prawns of any size group can bedried provided in the case of medium and big size prawns they arebeheaded prior to drying. In all size groups, beheading prior todrying results in better appearance of the end product in addition tothe output of the dryer per charge being increased.